PROSES PEMBELAJARAN TAHFIDZ AL-QUR’AN MENGGUNAKAN METODE TALAQQI DI SMP IT BAITUL MUSLIM: Muhammad Ridwan - Muhammad Ridwan (LPPM STAI Darussalam Lampung, 2022)
Abstract This study aims to determine the process of learning tahfidz using the talaqqi method at SMP IT Baitul Muslim Way Jepara. This type of research is qualitative research. The research instruments used in this study were interviews and observations. Based on the research results obtained from interviews and observations, there are 3 stages in the tahfidz learning process using the talaqqi method at SMP IT Baitul Muslim Way Jepara, namely the planning stage, implementation stage and solving obstacles in implementation. The tahfidz learning process using the talaqqi method has the advantage that the teacher is more free to supervise the development of his students directly. In addition, children can see directly the movements of the educator's lips in pronouncing makhorijul letters because they are dealing directly. While the drawback of the talaqqi method is that it cannot be used classically because it is less effective. In addition, students will feel bored waiting for their turn to be tested by rote by the teacher because the teacher has to test individually.